Whole-Genome Analysis of Halomonas sp. Soap Lake #7 Reveals It Possesses Putative Mrp Antiporter Operon Groups 1 and 2. (19th June 2019) - Mormile, Melanie R; Edwards, Tiffany; Frank, Ron; Geurin, Zachery; Haendiges, Julie; Hoffmann, Maria; Miller, Jesse
Abstract: The genus Halomonas possesses bacteria that are halophilic or halotolerant and exhibit a wide range of pH tolerance. The genome of Halomonas sp. Soap Lake #7 was sequenced to provide a better understanding of the mechanisms for salt and pH tolerance in this genus. The bacterium's genome was found to possess two complete multiple resistance and pH antiporter systems, Group 1 and Group 2. This is the first report of both multiple resistance and pH antiporter Groups 1 and 2 in the genome of a haloalkaliphilic bacterium.